Progress on Catastrophic Health Spending in 133 Countries : A Retrospective Observational Study - Wagstaff, Adam; Flores, Gabriela; Hsu, Justine; Smitz, Marc-François; Chepynoga, Kateryna; Buisman, Leander R.; van Wilgenburg, Kim; Eozenou, Patrick (Elsevier, 2018)
The goal of universal health coverage (UHC) requires inter alia that families who get needed health care do not suffer undue financial hardship as a result. This can be measured by the percentage of people in households whose out-of-pocket health expenditures are large relative to their income or consumption. We aimed to estimate the global incidence of catastrophic health spending, trends between 2000 and 2010, and associations between catastrophic health spending and macroeconomic and health system variables at the country level.